Internal personal resources in patients with different types of alopecia: the role of hardiness and resilience in mental maladaptation - Chemerys, Maryana (Psychosomatic Medicine and General Practice, 2025)
Background. Alopecia is not only a dermatological condition but also a significant psychosocial challenge associated with body image disturbance, reduced quality of life, and increased risk of anxiety and depressive disorders. Within the framework of psychodermatology, internal adaptive resources, particularly hardiness and resilience, are considered key determinants of stress coping and psychological adjustment. However, their role in the development of psychological maladaptation in patients with alopecia remains insufficiently explored. Objective. To assess the characteristics of hardiness and resilience as internal adaptive resources in patients with different types of alopecia and to determine their association with the level of psychological maladaptation. Materials and methods. Women with metabolic (n=45) and mixed (n=108) alopecia were examined. Hardiness was assessed using the short version of the S.R. Maddi Hardiness Test, and resilience was measured using the Connor–Davidson Resilience Scale (CD-RISC-10). Comparative analysis was performed depending on the type of alopecia and the severity of psychological maladaptation. Results. Patients with mixed alopecia demonstrated significantly lower total hardiness scores (21.98±3.54) compared to those with metabolic alopecia (26.47±5.05; p<0.01). Similar patterns were observed across all hardiness components: commitment (6.93±1.85 vs 7.67±2.03; p<0.05), control (7.43±2.66 vs 9.33±3.02; p<0.01), and challenge (7.63±1.81 vs 9.47±1.97; p<0.01). Resilience levels were also significantly lower in the mixed alopecia group (17.05±7.60 vs 25.36±6.48; p<0.01). A clear gradient relationship was identified between the severity of psychological maladaptation and internal adaptive resources: hardiness decreased from 27.49±4.18 (no maladaptation) to 18.37±1.77 (maladaptation disorders; p<0.01), while resilience declined from 23.02±8.26 to 14.43±6.56 (p<0.01). The most sensitive components of hardiness were commitment and control. Conclusions. Hardiness and resilience represent key internal adaptive resources that determine psychological adjustment in patients with alopecia. Their reduction is associated with the development of psychological maladaptation and may serve as a predictor of its severity. These findings support the integration of resource-based assessment into clinical psychological evaluation and the development of targeted interventions aimed at strengthening adaptive capacities. Keywords: alopecia; mental maladaptation; psychodermatology; hardiness; resilience; adaptive resources; quality of life; body image УДК 616.891:616-052:615.851